Artes visuais, literatura infantil e a educação nos livros de artista para crianças - Milene Brizeno Chalfum (2018)
This research, in the area of education and language, presents correlations - theoretical, formal, material and procedural - between the picturebooks of contemporary children's literature and the artists books, category and work of the visual arts. It was based on the the premise that the proximity of these works and the composition of a shared territory of ideas between their fields of knowledge could open for picturebooks new looks, interpretations and uses. The course of the investigation was constituted under the lens of the artists books, beginning with the elaboration of a theoretical construct referenced by Paulo da Silveira, Edith Derdyk, Amir Brito Cadôr, Júlio Plaza, Clive Phillpot, and Ulises Carrión, about the object book and the works of the category in a broad and strict sense: edited artists books and artists books for children. Then, it was made an approach of the picturebooks by the art of illustration and narrative according to the conceptions of Odilon Moraes, Rui de Oliveira, Peter Hunt and Sophie Van Der Linden, as well as the building of an inter-relational and intermedia space between picturebooks and artists books in an interart perspective realized according to the propositions of Claus Clüver and Fábio Morais, among others of its proponentes. The analysis corpus consisted, comparatively, by two large collection groups: on one side, the "Special collection of artists books of the UFMGs library; from the other, Bebeteca and Research Group on Literary Literacy - Gpell, members of NEPEI and CEALE / FaE of UFMG. Similarities were observed among the works given by the system of assembly and structuring of the book object, in the affinity of material and conceptual poetics and in the offer of unusual ways of reading and manipulation. They are reflexive tangencies that reverberate in the artistic and literary experience of the book object, amplifying its aesthetic, cultural and educational potentials.